IMPLEMENTATION OF THE TRIPLE BOTTOM LINE PRINCIPLE IN THE DEVELOPMENT OF GUNUNG NONA TOURISM ATTRACTION IN ENREKANG REGENCY - Jasman Jasman; Masri Ridawan; Muhammad Musawantoro (Geographica: Science and Education Journal, 2025)
The Triple Bottom Line (TBL) concept emphasizes that in managing an organization, attention is not only given to the financial aspect (Profit), but must also contribute to society (People) and play an active role in preserving the environment (Planet). The triple bottom line approach is very relevant for the development of Tourist Attractions, with the aim of integrating the interests of society, the environment, and improving economic welfare. This study aims to apply the triple bottom line concept in the management of the Gunung Nona Tourist Attraction in Enrekang Regency. Data collection methods used include documentation studies, in-depth interviews, and observations. Data analysis was carried out using qualitative descriptive techniques. The results of the study indicate that the management of the Gunung Nona Tourist Attraction in Enrekang Regency will be more effective if the Triple Bottom Line Model approach is applied. However, the managers of the Tourist Attraction have implemented the principles of TBL, but in reality it still needs to be improved, especially in terms of community involvement and environmental management. Keywords: Tourism Attraction Development, Triple Bottom Line, Mount Nona